LEMBAGA PEMASYARAKATAN BERWAWASAN HAK AZAZI MANUSIA BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2022 TENTANG PEMASYARAKATAN - Heriyanti, Yuli; Luthfi, Amir; Zikri, Ahmad (Jurnal Pahlawan, 2024)
Law Number 22 of 2022 concerning Corrections, in Article 1 number 18 states that "Correctional Institutions hereinafter referred to as Lapas are institutions or places that carry out the function of Guidance for Prisoners". Human Rights are also the nature of humans themselves who were born and created by the Creator, God Almighty. This research is a descriptive normative legal research. Based on Law Number 22 of 2022 concerning Corrections, there are principles of guidance carried out by Correctional Institutions and several forms of guidance that are oriented towards Human Rights. Furthermore, it was found that the principles of guidance and forms of guidance for prisoners or inmates are a form of recognition of the existence of Human Rights. Keywords: Development, Correctional Institutions, Human Rights